Implementasi Kebijakan Bersosial Media untuk Mengurangi Dampak Negatif pada Siswa SMAN 1 Ciruas - Sultan Hadiwijaya; Aisah Fitri; Ludiyah Ludiyah; Rizki Dwi Febriansya; Farah Rahmawati; Nindi Riyan Gustin (Lembaga Pengembangan Kinerja Dosen, 2026)
This Community Service (PKM) activity was carried out as a response to the high penetration of social media use among teenagers, especially SMAN 1 Ciruas students, which has the potential to have a negative impact if not balanced with adequate behavioral governance and internal regulations. The phenomena identified include gadget addiction (nomophobia), cyberbullying, the spread of fake news (hoax), decreased study concentration, and the risk of digital privacy violations in the form of identity theft. The main purpose of this activity is to provide education, socialization, and initiate a wise, healthy, and safe social media governance policy framework to build the resilience of the digital ecosystem in partner schools. The implementation method consists of two stages, namely preparation through observation and coordination with the school, as well as the implementation of participatory educational-seminars that integrate legal materials of the ITE Law and digital ethics with a focused group discussion forum based on case studies. The target audience is 75 students in grades X and XI as class representatives and administrators of the organization. The results of the activity showed a significant increase in the understanding of social media ethics, the ability to think critically about cyber risks, and the commitment to privacy protection which was realized through the